Real-Time Web-Based GIS and Remote Sensing for Flood Management - Md. Taibur Rahman; khan Rubayet Rhaman (The Institute for Research and Community Services, Institut Teknologi Bandung, 2005)
Keywords: GIS, remote sensing, flood, management